Dynamic aiming strategy for central receiver systems. (December 2021) - Speetzen, N.; Richter, P.
Abstract: Aiming strategies in central receiver systems search for an optimal assignment between heliostats and aim point on the receiver surface. In this work, we develop an accelerated aiming strategy which can be used for dynamic scenarios such as short-term environmental influences. The strategy bases on the linear formulation of the problem. To achieve a performance close to real-time, we present several accelerations based on carefully chosen methods to reduce the problem size. The performance of different solvers is evaluated and the problem reduction is adjusted according to accuracy, prediction time and computational run-time. The accelerated aiming strategy is applied to central receiver systems with up to 8600 heliostats in a dynamic test scenario with cloud shadows passing over the heliostat field. The accelerated aiming strategy is effective enough to be used as a real-time control strategy.